Rheological characteristics of EVA modified bitumen and their correlations with bitumen concrete properties - Brovelli, Claudio (2013)
Polymer modified bitumens (PMBs) were prepared by mixing bitumen from two different sources with an EVA copolymer. The rheological characteristics of the PMBs were analyzed using small amplitude oscillatory shear and steady shear tests. Data were analyzed with rheological models developed for particle suspensions and with Palierne’s model for polymer blends. Results indicate that such models cannot account for the EVA modification of the bitumen in the whole range of temperatures, frequencies and shear rates studied. The effects of EVA on the PMBs viscoelastic properties and morphology depend on the type of bitumen considered. However, power law relationships between the rheological functions of PMBs and the Young complex modulus and the rut depth of corresponding mastics are identified.